Teleconsultation in health and social care professions education: A systematic review. (27th July 2022) - Wetzlmair, Lisa‐Christin; O'Carroll, Veronica; O'Malley, Andrew S.; Murray, Stuart
Abstract: Introduction: Teleconsultation education in health care and social work education is under‐reported. However, literature indicates that educating the workforce in teleconsultation skills is essential to continue with safe, high‐quality delivery of services and increases the likelihood of implementing teleconsultations in health care. Training for students should, therefore, be encouraged. This systematic literature review aims to investigate global experiences of teleconsultation training in undergraduate health care and social work education. Methods: A systematic review of peer‐reviewed literature was undertaken. The review was guided by the Joanna Briggs Institute guidelines. Electronic databases were searched for eligible evidence. Studies were included only if they described and evaluated teleconsultation education for undergraduate health care and social work students. Results/Discussion: This review shows that mandatory education in teleconsultation is limited in undergraduate health care and social work education. Narrative synthesis and analysis of 14 studies led to the development of two themes: pedagogical aspects, and perspectives on telecommunication and teleconsultation learning and teaching. Practical experiences with simulated patients or during clinical placements with real patients were the most common mode of delivery. Feedback on teleconsultation education was generally positive; overall, health care students felt more confident using teleconsultation and valued safety of learning through simulation. Conclusion: Teleconsultation education is a legitimate way to expose students to telehealth. High satisfaction rates, increased knowledge and confidence in use indicate the positive impact this learning has on students. Nevertheless, further high‐quality research and guidance for educators are warranted.